Clinical Profile of TB in Children at Pediatric Outpatient Clinic Hasan Sadikin Hospital Bandung 2016 - Fadiya N Soekotjo; Sri Sudarwati; Anggraini Alam (Universitas Kristen Maranatha, 2019)
The diagnosis process of TB in children is complicated. Bacteriological exam is needed to establish diagnosis, but it is not possible to be done in children. Clinical symptoms are the main criteria for TB diagnosis in children. This study aimed to provide clinical profile of TB in children and was conducted using descriptive design. The data was taken from medical record of children with TB at RSHS pediatric outpatient clinic from January 2016 to December 2016. We collected 104 subjects using simple random sampling method. We found out that 64 subjects (61.54%) was diagnosed as lung TB and 40 (38.46%) with extra-pulmonary TB. Contact with the source of transmission was found in 33 patients (60%). We found that clinical symptoms of the subjects were fever 2 weeks (62.5%), weight increase difficulty (49%), lymphnode enlargement (36.5%), cough >= 2 weeks (14.4%), chest tightness (7.7%), bone swelling (4%), and night sweats (2%). We concluded that clinical symptoms that are found mostly in children with TB are fever >= 2 weeks, weight increase difficulty, lymphnode enlargement, cough >= 2 week, chest tightness, bony swelling, and night sweats. Keywords: clinical profile, tuberculosis, TB infection in children